Investigation and Finite Element Analysis of The Distal Weight-Bearing Implant: Investigasi dan Analisis Elemen Hingga dari Implan Penahan Berat Distal - Muntadher Saleh Mahdi; Dunya Abdulsahib Hamdi (Academia Open, 2024)
General Background: Osseointegration. a critical advancement in prosthetics, significantly benefits individuals with transfemoral amputations by enhancing their quality of life through innovative implant systems. Specific Background: The study examines a novel distal weight-bearing implant from 17 global systems, featuring a composite nanocoating of hydroxyapatite and silica, evaluated through finite element analysis and mechanical testing. Knowledge Gap: Research on nanocoating's impact on mechanical performance and its integration into advanced prosthetic designs is limited, despite extensive exploration of various implant systems. Aims: The study evaluates the distal weight-bearing implant's effectiveness, focusing on the nanocoating's role in shock absorption and mechanical stability during various gait cycle phases. Results: The design process involved creating a Ti-6Al-4V femoral stem and UHMWPE spacer, with the implant subjected to FEA under gait cycle conditions. Nanocoated samples demonstrated effective shock absorption, though with slightly reduced mechanical properties. The implant’s performance was evaluated for heel strike, midstance, and pre-swing phases, showing adequate load-bearing capacity within safe thresholds. Novelty: This study introduces a detailed analysis of nanocoating impacts on implant performance and integrates biomechanical forces into FEA for enhanced prosthetic design evaluation. Implications: Research indicates nanocoating enhances shock absorption, but further studies are needed to balance mechanical properties with biocompatibility and biological response, potentially improving amputee care outcomes. Highlights: Advanced Implant Design: Transition from transfemoral to knee disarticulation. Nanocoating Impact: Enhances shock absorption; minor mechanical property reduction. FEA Results: Confirms load-bearing capacity through gait cycle phases. Keywords: osseointegration, distal weight-bearing implant, nanocoating, finite element analysis, gait cycle